The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4028/www.scientific.net/ssp.307.104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CeO<sub>2</sub> Nanoparticle on the Structural and Electrical Properties of BSCCO-2223 High Temperature Superconductor

Abstract: A study of the effects of Cerium oxide nanoparticle doped with BSCCO-2223 on the microstructure and superconducting properties was carried out. All samples were synthesized using solid state reaction method. Ce concentration is varied from x = 0.0 up to 0.1 in a general stoichiometry of Bi1.6Pb0.4Sr2Ca1-xCexCu3Oy. The samples were characterized structurally and electrically by X-Ray Diffraction (XRD) and four-point probe method respectively. XRD analysis shows that both (Bi,Pb)-2212 and (Bi,Pb)-2223 phases coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It can be concluded that the blossom of the US-SnO2 nanoparticle, from spherical to a huge needle-like cluster, affects negatively the formation of the Bi-2223 phase [21]. The Jc(B) of the samples at 65 K was calculated by the modified Bean model: Jc = 20ΔM/[a(1b/3a)] and presented in Figure 4 [2,5,22]. The contrariant influences were found in the series' two types of SnO2 nanoparticle doping.…”
Section: Superconducting Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be concluded that the blossom of the US-SnO2 nanoparticle, from spherical to a huge needle-like cluster, affects negatively the formation of the Bi-2223 phase [21]. The Jc(B) of the samples at 65 K was calculated by the modified Bean model: Jc = 20ΔM/[a(1b/3a)] and presented in Figure 4 [2,5,22]. The contrariant influences were found in the series' two types of SnO2 nanoparticle doping.…”
Section: Superconducting Propertiesmentioning
confidence: 99%
“…Numerous investigations have been conducted on the Bi2Sr2Can-1CunO2n+4+δ (BSCCO) hightemperature superconductor system since its discovery, aiming to enhance its superconducting properties [1][2][3]. The BSCCO system consists of three distinct superconducting phases, namely Bi-2201 (n = 1), Bi-2212 (n = 2), and Bi-2223 (n = 3), with corresponding critical temperatures (Tc) of 33 K, 80K, and 110 K, respectively [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation